Recent advances in dopaminergic strategies for the treatment of Parkinson’s disease - Mao Qi; Qin Wang-zhi; Zhang Ao; Ye Na (Acta Pharmacologica Sinica, 2020)
Parkinson’s disease (PD) is the second most common progressive neurodegenerative disease worldwide. However, there is no available therapy reversing the neurodegenerative process of PD. Based on the loss of dopamine or dopaminergic dysfunction in PD patients, most of the current therapies focus on symptomatic relief to improve patient quality of life. As dopamine replacement treatment remains the most effective symptomatic pharmacotherapy for PD, herein we provide an overview of the current pharmacotherapies, summarize the clinical development status of novel dopaminergic agents, and highlight the challenge and opportunity of emerging preclinical dopaminergic approaches aimed at managing the features and progression of PD.